2016
DOI: 10.1111/acer.13033
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Contextual Factors, Alcohol Use, and Alcohol Problems in the United States: Evidence From a Nationally Representative Study of Young Adults

Abstract: Background There is considerable variation in alcohol use and problems across the United States, suggesting that systematic regional differences might contribute to alcohol involvement. Several neighborhood contextual factors may be important aspects of this “alcohol environment.” Methods Participants were 15,197 young adults (age 18–26) from Wave III of the National Longitudinal Study of Adolescent to Adult Health, a nationally-representative United States survey. Measures of past-year alcohol use and probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 40 publications
5
31
0
1
Order By: Relevance
“…Conversely, many studies have found that, among adults, those in urban areas have higher rates of alcohol use compared to those in rural areas (Dixon and Chartier 2016; Slutske et al 2016). Comprehension of different drinking trajectories across the life course, in terms of urban/rurality, is needed to explain this pattern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, many studies have found that, among adults, those in urban areas have higher rates of alcohol use compared to those in rural areas (Dixon and Chartier 2016; Slutske et al 2016). Comprehension of different drinking trajectories across the life course, in terms of urban/rurality, is needed to explain this pattern.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the sample was made up of 15-year-olds; therefore, findings of an urban/rural gradient in having ever drunk represent a more delayed initiation to drinking but do not necessarily translate to lifetime abstention throughout adulthood. Conversely, many studies have found that, among adults, those in urban areas have higher rates of alcohol use compared to those in rural areas (Dixon and Chartier 2016 ; Slutske et al 2016 ). Comprehension of different drinking trajectories across the life course, in terms of urban/rurality, is needed to explain this pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associations between drinking pattern and demographic features, like age and sex, as well as neighborhood contextual factors, have been observed. A study of 15 197 young adults living in the USA has shown that more advantaged and educated people living in urban neighborhoods with higher densities of places selling alcohol have higher alcohol involvement among people 18–26 years olds [ 12 ]. However, a recent study among young white and black women in the USA revealed that ethno-cultural diversity also significantly influences alcohol use [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Families residing in rural areas are more likely to be living in poverty than families living in urban areas (Kusmin 2016; Miller and Rowley 2002). Although there is not a consistent association between socioeconomic status and alcohol use in adolescence (Hanson and Chen 2007; Slutske et al 2016), it is plausible that the expression of the genetic propensity to use alcohol may be restricted among those with limited financial means to purchase alcohol.…”
Section: Introductionmentioning
confidence: 99%